A work in progress - accreditation of forensic DNA laboratories as a part of the, , European Forensic Science Area 2020 (EFSA 2020)" concept. Issue 1 (December 2019) - Nogel, Mónika; Czebe, András; Kovács, Gábor; Pádár, Zsolt
Abstract: As 2020 is approaching, various stakeholders and EU Member States are currently implementing some elements of the EFSA2020 concept. EFSA2020 offers Europe the chance to raise the quality level of its forensic science and in doing so, improve the public's confidence in the administration of justice. However, there is plenty of opportunity for further progress in creating the common forensic area. The paper will focus on accreditation of forensic DNA laboratories in V4 countries.